2011
DOI: 10.1117/1.3582334
|View full text |Cite
|
Sign up to set email alerts
|

Multiexposure laser speckle contrast imaging of the angiogenic microenvironment

Abstract: Abstract.We report the novel use of laser speckle contrast imaging (LSCI) at multiple exposure times (meLSCI) for enhanced in vivo imaging of the microvascular changes that accompany angiogenesis. LSCI is an optical imaging technique that can monitor blood vessels and the flow therein at a high spatial resolution without requiring the administration of an exogenous contrast agent. LSCI images are obtained under red (632 nm) laser illumination at seven exposure times (1-7 ms) and combined using a curve-fitting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
(33 reference statements)
1
17
0
Order By: Relevance
“…Significant increase was observed in samples obtained from animals submitted to laser therapy alone and combined with S. chilensis. These results agree with the literature reporting that laser therapy stimulates angiogenesis [63,64]. In the present study, we observed that the same did not occur on the applications with the S. chilensis extract alone which probably indicates that the angiogenic effect is due to the action of the laser.…”
Section: Discussionsupporting
confidence: 92%
“…Significant increase was observed in samples obtained from animals submitted to laser therapy alone and combined with S. chilensis. These results agree with the literature reporting that laser therapy stimulates angiogenesis [63,64]. In the present study, we observed that the same did not occur on the applications with the S. chilensis extract alone which probably indicates that the angiogenic effect is due to the action of the laser.…”
Section: Discussionsupporting
confidence: 92%
“…The speckle ICTs are computed by fitting each curve to equation (2) and enable mapping of the flow dynamics by analyzing the characteristic shapes of these curves. It is important to note the inflections in the speckle variance curves, as multiexposure implementations with fewer exposures 36,37 congregated in one or two decades of exposure duration may insufficiently capture this relationship and thereby inaccurately sample the flow distributions present, especially after induced flow changes. A true MESI ICT image of flow is generated from the 15 single-exposure speckle images in Figure 2B.…”
Section: Resultsmentioning
confidence: 99%
“…Thinned skull preparation also has benefits like simpler surgical preparation and better control of intracranial pressure. For the thinned skull preparation, the standalone micro-imager can be updated with the multi-exposure strategy [29,30] for a robust CBF measurement.…”
Section: Multi-exposure Lsci and Thinned Skull Preparationmentioning
confidence: 99%